The condensed handbook of measurement and control - Battikha, N. E. (ISA, 2018)
"Selecting and implementing measurement and control devices for process automation applications is made easier with this best-selling reference. This clear and concise fourth edition provides quick access to ISA symbology, instrument and control valve selection criteria, and conversion guidelines, with new sections on maintenance, calibration, decision-making skills, and consulting. Whether you are an experienced engineer, technician, salesperson, or project manager, or new to the field, you will better understand how to assess, compare, and select the various methods of measurement and control with this valuable and economical handbook in your library."--Back cover